Storage Behaviour of Guava Fruits in Evaporative Cool Chambers during Winter Season - Singh, Yogender; YADAV, Y K (Journal of Agricultural Engineering, 2013)
Shelf life of guava in evaporative cool chamber during winter was evaluated on the basis of physiological lossin mass, acidity, total soluble solids and ascorbic acid. Results indicated that the evaporative cool chamberscould be an ideal on-farm storage facility for maintaining quality and overall acceptability of guava. Theaverage difference in dry bulb air temperature between ambient and evaporative cool chamber with river bedsand (ECC RBS) was 8.1 ºC, and between ambient and evaporative cool chamber with rice husk ash (ECC RHA)was 9.0 ºC during storage. Guava fruits stored in cool chamber had double shelf-life as compared to storageunder ambient condition, and also had high organoleptic score. The evaporative cool chamber with risk huskash was found to be more effective in reducing dry bulb temperature, elevation in relative humidity and increasein cooling efficiency than evaporative cool chamber with river bed sand.